From Berlin to Belém: Theodor Koch-Grünberg's Rio Negro collections. Issue 1 (2nd January 2019) - Petschelies, Erik
ABSTRACT: During his expedition to the rivers Rio Negro and Japurá between 1903 and 1905, the German ethnologist Theodor Koch-Grünberg amassed an ethnographic collection. Part of it he sold to the Royal Museum of Ethnology in Berlin and a smaller part was purchased by the Swiss naturalist Emílio Goeldi for the Museu Paraense in Belém, in northern Brazil. A number of aspects arise from this singular transaction: research funding (including institutional and personal relations) at the beginning of the institutionalisation of anthropology; the importance of German speaking intellectuals to the development of natural sciences and ethnography of Brazil; the social and economic importance of collecting and the complexity of local political relations. The aim of this article is to analyze the social context in which this collection was formed, with special attention to the indigenous agency and social relations around material culture. It seeks to contribute to the history of collections, the history of science in Brazil and of the transatlantic relations between Brazilian museums and German ethnology.